Antimicrobial efficacy of photodynamic therapy against streptococcus mutans bioflim on orthodontic brackets an in vitro study /Maria Angelica B. Barrameda ; thesis - Barrameda, Maria Angelica B.; Tan-Zafra, Josievitz
Introduction: Orthodontic brackets predispose accumulation of dental biofilm causing caries and gingivitis. Mechanical removal of plaque serves as the primary treatment. As adjunct, Chlorhexidine is used but has side-effects like tooth staining and bacterial resistance due to long term use. This study aimed to test the efficacy of another treatment modality to reduce the number of S. mutans in dental biofilm on orthodontic brackets, the Photodynamic Therapy. This involves a photosensitizer activated but light with a specific wavelength producing reactive oxygen species, which kill the bacteria.
Materials and Methods: A 5-day S. mutans biofilm was grown on metal brackets bonded to bovine enamel slabs (40 samples). Thirty-nine specimens were randomized to 3 treatment groups: A Distilled Water; B. 0-12% Chlorhexidine (CHX); C. Photodynamic Therapy (PDT) using Toluidine Blue O as photosensitizer and red LED (630nm). After treatment, one speimen from each group was randomly chosen and viwed under Environmental Scanning Electron Microscopy (ESEM) to determine the biofilm morphology. From the other 12 specimens, biofilms were collected, weighed and cultured onto BHI agar plates to determine the number of colony forming units per milligram (CFU/mg). For baseline evaluation, one clean and one untreated specimen were preserved for ESEM evaluation.
Results: The significance of differences among groups was determined using Tukey HSD test. Group A had the most S. mutans count (37.0573 CFU/mg) and was significantly different (p<0.05) from groups B (0.1712 CFU/mg) and C (1.1193 CFU/mg), were both groups had less bacteria than group A. The statistical difference between Groups B and C was not significant. ESEM images showed specimen A covered with more abundant and denser S. mutans biofilm that specimens B and C. The difference of biofilm morphology between specimens B and C was hardly noticeable.
Conclusion: Based on this study, Photodynamic therapy and 0.12% Chlorhexidine resulted in significant S. mutans reduction based on the number of CFU/mg. There was no significant difference between PDT and 0.12% CHX. Photodynamic therapy could be an alternative adjunctive tool to mechanical removal of plaque adhered to orthodontic brackets.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Chlorhexidine; Streptococcus mutans; Photodynamic Therapy; Dental Biofilm